Estudo sociocultural da comunidade discursiva do tratamento temático da informação em bibliotecas universitárias - Dal´Evedove, Paula Regina [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2013)
It is assumed as a sociocultural approach to contemporary theories necessary to scientific Information Science, considering that information should be treated from the observance of its context of enunciation, situations and purposes, involving all social actors. In this sense, it is the prerogative of the individual knowledge is socially conditioned and therefore it becomes necessary to investigate the knowledge of professionals who directly or indirectly influence the products generated in the thematic treatment of information in context of university libraries. To do so, it explores the discursive community of thematic treatment information from the institutional and social interaction through structured interview. The results revealed the need of Information Science advance the establishment of studies that surround issues involving human action from the social reality in order to enhance the theoretical concepts and methodological thematic treatment of information in context of university libraries.

Parte-se da prerrogativa de que o conhecimento individual é socialmente condicionado e, por isso, torna-se necessário investigar o conhecimento dos profissionais que influenciam direta ou indiretamente os produtos gerados no tratamento temático da informação em contexto de bibliotecas universitárias. Para tanto, analisa-se a comunidade discursiva do tratamento temático da informação a partir do contexto institucional e interação social por meio de entrevista estruturada. Os resultados revelaram a necessidade da Ciência da Informação avançar no estabelecimento de estudos que cerquem questões que envolvam a ação humana a partir da realidade social objetiva, a fim de aprimorar as concepções teóricas e metodológicas do tratamento temático da informação em contexto de bibliotecas universitárias.
Study sociocultural community discursive treatment of thematic information in the university libraries
Keywords: abordagem sociocultural; tratamento temático da informação; biblioteca universitária